Surface Polysaccharide from Staphylococcus aureus M That Contains Taurine, d-Aminogalacturonic Acid, and d-Fucosamine - Liau, Deng-Fong (1974)
The surface polysaccharide antigen of Staphylococcus aureus M was isolated, and the component parts were identified. The antigen is composed of taurine, d-aminogalacturonic acid, and d-fucosamine. The capsule is chemically distinct from all previously reported staphylococcal capsules. Taurine and aminogalacturonic acid have not been reported previously in staphylococci.